(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Bhaishajya Kalpana- the pharmaceutical science of Ayurveda mainly deals with the planning and preparation of medicines. As per Ayurveda, an ideal drug is that one which can process into different forms. Though Ayurveda claims that no material is incapable of being utilized as medicine, none of them can be employed in the form in which they are available because they are not appetizing or easily absorbed by the human system. In this modern era, society prefers medicines which are more palatable, available, less dose and with more shelf life. In this view, as per the need of time, there is a need to modify the classical formulations in order to improve its characters and to make more acceptable. In this present study, Tiladi churna, a pure herbal formulation having minimum ingredients and its granules were prepared in departmental pharmacy. Churna Kalpana is considered as an Upakalpana of Kalka Kalpana which is one among the basic Panchavidha Kashaya Kalpana mentioned in classical texts while Khanda Kalpana or granules are the preparations added after 20th century which have more palatability and acceptance. Here both Tiladi Churna and granules were then compared to determine the efficiency in terms of method, duration of preparation and also in terms of organoleptic and physical parameters